FTIR Analysis of a Light‐driven Inward Proton‐pumping Rhodopsin at 77 K1. (22nd June 2017) - Ito, Shota; Sugita, Shinya; Inoue, Keiichi; Kandori, Hideki
Abstract: Parvularcula oceani xenorhodopsin ( Po XeR) is a light‐driven inward proton pump that was discovered from deep ocean marine bacteria. Po XeR is categorized into the same family of Anabaena sensory rhodopsin (ASR) that functions as a photochromic sensor. In this study, we applied light‐induced difference Fourier‐transform infrared (FTIR) spectroscopy to Po XeR at 77 K, and the obtained spectra were compared with those of ASR. The structure and structural changes in the primary processes of Po XeR are common to all microbial rhodopsins. The red‐shifted K formation ( Po XeRK ) was accompanied by retinal photoisomerization from the all‐ trans to 13‐ cis form resulting in a distorted structure of the retinal. The observed hydrogen out‐of‐plane (HOOP) vibrations were sensitive to H/D exchange, indicating that the chromophore distortion by retinal isomerization is located near the Schiff base region in Po XeR. The hydrogen‐bonding strength of the protonated Schiff base is similar between Po XeR and ASR, whose acceptor is presumably a water molecule. Unlike ASR, however, Po XeR contains strongly hydrogen‐bonded water (O‐D stretch at 2277 cm −1 in D2 O), which is also the case for outward proton pumps. The detailed structure, structural changes upon retinal photoisomerization, as well as functional correlation in Po XeR are discussed based on the present FTIR study. Abstract : Parvularcula oceani xenorhodopsin ( Po XeR) is a recently discovered light‐driven inward proton pump from deep ocean marine bacteria. Po XeR is categorized into the same family of Anabaena sensory rhodopsin (ASR), a photochromic sensor, whose amino acid identity is 51 %. In this study, we applied light‐induced difference Fourier‐transform infrared (FTIR) spectroscopy to Po XeR at 77 K, and the obtained spectra were compared with those of ASR. Similar N‐D stretch of retinal Shiff base and different O‐D stretch of water molecules between Po XeR and ASR are discussed based on the present FTIR analysis.